AN ANALYSIS OF SLANG ON TWITTER IN INDONESIA - Setyowati, Ratini; Yanottama , Fourica (LPPM Universitas Duta Bangsa Surakarta, 2023)
Technology provides both exciting opportunities and complex challenges that influence human’s life, one of the influences is language changes. This paper aims to provide the reader with an understanding of the slang types on social media, especially Twitter. This paper applies qualitative data research to discover and research types of slang and why it is used for interactions. Data were collected from document analysis and used the interactive model of data analysis. The results shows that the types of slang language on Twitter showed different results for each type. The highest is acronyms with a percentage of 78,57% and the least are imitative, compounding, and clipping with a percentage of 1,42%. There were 2 reasons for using slang, the reasons is to build a good impact on social interaction, and to use slang language to make the conversation run much more smoothly. The conclusion of this study is people use a variety of languages from formal language to informal. One of language variations is slang on social media or even in daily conversations with types of slang such as fresh and creative, imitative, compounding, clipping, and acronyms.